The Direct and Indirect Effect of Zakat on the Household Consumption of Mustahik (A Study of Zakat Recipients from BAZNAS Probolinggo Municipality) - Elok Nurlita; Marlina Ekawaty (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
This researchaimsto analyze the direct and indirect effects of zakat on the household consumption of mustahik. The research adopts a quantitative approach and usespath analysis. Data were obtained from 50 mustahik (zakat recipients)at BAZNAS Probolinggo Municipalityusing theproportional random sampling method. The results show that zakat and number of household members directly and indirectly affect the household consumption of mustahik. Furthermore, household income as an intermediate variable also affects the household consumption of mustahik, whereas education and age have no effect, either directly or indirectly. The lackof effect of education on consumption can be attributed to the mustahiks’ jobs, for which no education/special skills are required;thus, a high level of education does not affect household income and consumption. Similarly, the lack of effect of age on predicted consumption is because many mustahik are not at a productive age and do not work;increasing age does not therefore increase income and consumption. Keywords: Poverty, Consumptive Zakat, Productive Zakat, Household Consumption